Simulation of an Induction Machine for Electric Vehicle Purpose - Characterization and Modelling of a High Torque Density Induction Traction Machine - Gámez Sánchez, Eric; Sarangi, Tapas (My University, 2017)
In this thesis, a currently used on automotive induction machine is studied. A model with two different software programs is set up in order to understand its full behaviour. For creating the model of the machine, different tests were done on the machine in order to obtain all the necessary parameters. In addition, using a well known smaller machine, a model was set up on the two different software programs in order to understand the calculations and for having a base case to compare with the commercial one. The results from the simulations in the two software and the measurements done on the machine were compared to validate the model. Some parameters matched well, as the powers, but others had some differences for variable working scenarios. The thesis resulted in different situations where the model can be used for a better understanding of the machine. In particular, the blocked rotor test was difficult to reproduce with one software.
Keywords: Elkraftteknik; Electric power engineering